The significance of research in quality of life in medicine - Trojanowska , Alina (Polish Journal of Public Health, 2011)
The term , quality of life” is an expression existing in many scientific disciplines, such as: philosophy, psychology, sociology, economy and medicine. In medical aspect life quality is associated closely with physical, psychical and social domains of health that are affected by experiences, beliefs, expectations and human perception. The change of the approach to patients to more holistic one, resulted in the increase of interest in the patient’s subjective feelings that concern the person, the therapy and the existential problems defined generally as evaluation of life quality. They deal with satisfaction of the treatment results, evaluation of physical and psychical functioning as well as ability to play the professional, social and family role. The aim of the study is to present the significance of life quality research in medicine. The studies of life quality provide data on the situation of patients; they facilitate seeing the problems of patients and allow for taking up activities focused on solving them.